Potensi Penerapan Eco-City untuk Mitigasi Pandemi di Kota-Kota di Indonesia pada Masa Depan - Valendya Rilansari; Chrisna Trie Hadi Permana (Jurnal Wilayah dan Lingkungan, 2022)
The Covid-19 pandemic that is plagued worldwide, has prompted research from various fields to develop strategies to mitigate similar events in the future. In the context of urban planning, the concept of an Eco-City or ecology-based city is one of the concepts offered by the literature trend that has developed in recent times. This concept discusses the development and arrangement of cities by planning to ensure ecosystem balance. This research aims to do a literature review that systematically discusses the theories and policies of eco-cities implemented in various countries in Asia using a systematic review method. The stages of a systematic review of this research include: a) limiting the scope and definition of the problem with a scopus indexed, b) selection of search results for cities in Asia, and c) screening research based on the citation score and impact factor. In this study, the concept of Eco-City is discussed in relation to the ability of a city to mitigate pandemics that may recur in the future. This study summarizes all findings, facts, and dynamics presented in the literature referenced using Microsoft Excel and Nvivo12. Finally, the findings of this study are discussed in the context of their potential application in Indonesian cities, which are divided into five aspects: social, environmental, economic, infrastructure, and governance.